DISSOLUTION KINETICS OF FOSTERITIC OLIVINE AT 90-150°C INCLUDING EFFECTS OF THE PRESENCE OF CO2 - Hanchen M.; Prigiobbe V.; Storti G.; Seward T.M.; Mazzotti M. (My University, 2006)
The steady state dissolution rate of San Carlos olivine [Mg1.82Fe0.18 SiO4] in dilute aqueous solutions was measured at 90, 120, and 150 °C and pH ranging from 2 to 12.5. Dissolution experiments were performed in a stirred flow-through reactor, under either a nitrogen or carbon dioxide atmosphere at pressures between 15 and 180 bar. Low pH values were achieved either by adding HCl to the solution or by pressurising the reactor with CO2, whereas high pH values were achieved by adding LiOH. Dissolution was stoichiometric for almost all experiments except for a brief start-up period. At all three temperatures, the dissolution rate decreases with increasing pH at acidic to neutral conditions with a slope of close to 0.5; by regressing all data for 2 ? pH ? 8.5 and 90 °C ? T ? 150 °C together, the following correlation for the dissolution rate in CO2-free solutions is obtained:r = AaH+n exp fenced(frac(- Ea, RT))with A = 0.0854 (+0.67 to -0.076), the activation energy Ea = 52.9 ? 6.9 kJ mol-1 K-1, n = 0.46 ? 0.03 (R2 = 0.98) and r in [mol cm-2 s-1], based on a 95% confidence interval. Data were fitted to a shrinking particle model, being based on the assumption of surface controlled dissolution throughout the whole experiment, with dissolution extent varying from less than 1% up to complete dissolution, depending on the experimental conditions. In the presence of CO2 and at low pH, dissolution rates exhibited the same behaviour as a function of pH, however at pH > 5 the rate decreased much more rapidly with pH than in the presence of N2. The presence of citric acid, an organic ligand, increased dissolution rates in respect to the baseline HCl solution significantly.
Keywords: CARBON DIOXIDE; DISSOLUTION; EXPERIMENTAL MINERALOGY; FORSTERITE; REACTION KINETICS; STOICHIOMETRY